Analysis of the Cooperation Model Between Starbucks and Nestle - Lei, Li (Indonesian Journal Publisher, 2025)
The collaboration between Starbucks and Nestlé in 2018 exemplifies a strategic licensing model in the global coffee industry, combining Starbucks’ premium brand identity with Nestlé’s extensive distribution capabilities (Moreira and Vidor, 2024). This partnership aims to accelerate market expansion and innovation by leveraging complementary strengths: Starbucks focuses on retail excellence, while Nestlé manages global distribution of packaged coffee and tea products. The study analyzes the alliance’s strategic motivations, operational mechanisms (e.g., supply chain integration, quality control), and market impacts, including sales growth and brand perception. It highlights how this licensing agreement balances control and flexibility, offering insights into how multinational corporations navigate competitive landscapes through collaborative models. The research contributes to understanding effective partnership strategies in the food and beverage sector.